Enhanced sedimentation of elongated plankton in simple flows - Clifton, W; Bearon, R N; Bees, M A (IMA journal of applied mathematics, 2018)
Abstract Negatively buoyant phytoplankton play an important role in the sequestration of CO$_2$ from the atmosphere and are fundamental to the health of the world’s fisheries. However, there is still much to discover on transport mechanisms from the upper photosynthetic regions to the deep ocean. In contrast to intuitive expectations that mixing increases plankton residence time in light-rich regions, recent experimental and computational evidence suggests that turbulence can actually enhance sedimentation of negatively buoyant diatoms. Motivated by these studies we dissect the enhanced sedimentation mechanisms using the simplest possible 2D flows, avoiding expensive computations and obfuscation. In particular, we find that in vertical shear, preferential flow alignment and aggregation in downwelling regions both increase sedimentation, whereas horizontal shear reduces the sedimentation due only to alignment. However, the magnitude of the shear does not affect the sedimentation rate. In simple vertical Kolmogorov flow, elongated particles also have an enhanced sedimentation speed as they spend more time in downwelling regions of the flow with vertically aligned orientation, an effect that increases with the magnitude of shear. An additional feature is identified in horizontal Kolomogorov flow, whereby the impact of shear-dependent sedimentation speed is to cause aggregation in regions of high shear where the sedimentation speed is minimum. In cellular flow, there is an increase in mean sedimentation speed with aspect ratio and shear strength associated with aggregation in downwelling regions. Furthermore, spatially projected trajectories can intersect and give rise to chaotic dynamics, which is associated with a depletion of particles within so-called retention zones.